Prospect . 6. - de Gele Zaal, Gent (Gent : Noordstarfonds vzw, 1987)
De Keyzer, Carl ; Michiels, Daniel ; Michielsen, Bart ; Geirlandt, Toni ; Ronday, Lucien ; Brunenberg, Jo ; Schochaert, Dominique
Prospect . 6, De Gele Zaal, Gent, 20.11.1987 - 17.1.1988
boek